The German Schwulenwebegung and Rosa von Praunheim’s Films: an Approach to the 1970s Dissident Liberation Movements from the Point of View of Cultural Manifestations - Rubino, Atilio Raúl (Instituto de Estudios Avanzados - Universidad de Santiago de Chile, 2020)
This article deals with the connection between the German gay-lesbian liberation movements of the 1970s decade with cultural manifestations, especially with Rosa von Praunheim’s films, focusing mainly on the 1971 film Nicht der Homosexuelle ist pervers, sondern die Situation, in der er lebt (It is not the homosexual person who is perverse, but the situation in which they live). For this purpose, we shall first go through the 1970s gay-lesbian liberation movements and the particularities they had in Germany, showing a continuance in the subsequent emergence of the queer perspective; then, we shall analyze Praunheim’s film and its enormous influence in the social movements of the time and in the configuration of a Schwul counterculture. Nicht der Homosexuelle… stands out as a breaking point in the history of German sexual dissidence, for it addressed the collective, with a calling to abandon marginalization and organize for the struggle. The film proclaims the necessity of going out to fight for one’s rights, of leaving the sociability of toilets behind and starting to take to the streets, to make sexuality a public—and thus, a political—matter.